The Effects of Local Governmental Incomes, General Allocation Funding and Special Allocation Funding on Open Unemplyoment in West Java Province: A Panel Data Analysis from 2013 to 2020 - Jamiel, Harun Nur; Anwar, Nurul; Arifin, Agus (Proceeding ICMA-SURE; Proceeding The 5th International Conference on Multidisciplinary Approaches for Sustainable Rural Development, 2023)
The study aimes to investigate the contributions and effects of local govermental income, general allocation funding, and special allocation funding on open unemployment. Drawing on the West Java provincial panel data, the study sought to examine the relationships of the existing variables by means of panel data regression analysis. Results indicated Regional Original Income had a positive and significant effect on open unemployment in West Java Province.  The General Allocation Fund had a negative and significant effect on open unemployment in West Java Province. The Special Allocation Fund had a positive and significant effect on open unemployment in West Java Province.